Persepsi Pemilik Proyek Dalam Lingkungan LPSE Terhadap Penilaian Kinerja Kontraktor - Nurhidayati Nurhidayati; As’ad Munawir; Eko Andi Suryo (Rekayasa Sipil, 2017)
Good contractor performance can provide satisfaction for owners. The research is to identify factors influencing owners perception in assessing contractor performance in UB. Method of analysis using Importance Performance Analysis and Customer Satisfaction Index. The results of the analysis show satisfaction of 75.22% and 71.69% means that the owner is satisfied with the performance of their contractor. Attributes that are prioritized for improvement/improvement include: completion of work in accordance with the contract; the filing of MC-0 is done before the work begins; ability of human resources in handling material delays/scarcity, workers crisis, design change, environmental security, etc .; as well as the speed & willingness to repair the damaged buildings around the project site